Los awajún y wampís contra el Estado: una reflexion sobre antropología política - Regan Mainville, James (2010)
The strikes of the amazonian indigenous peoples in 2008 and 2009 revealed a kind of society little known in the rest of the country. These are egalitarian and acephalic peoples immersed in a bureaucratic State and surrounded by a stratified society. Some of the awajun leaders were interviewed and the history of this people was examined to understand the motivation and organizational principles of this movement.